The role of “citizen journalist” in the Arab revolution from the perspective of the elites in Arab media (Syria model) - Albostangy, Areej (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Arab Spring has been shaped by successive episodes of the revolutions of freedom, the largest geopolitical movement that has rocked the Arab world since the 1960s. This study aims at determining the role played by the citizen journalist in the Arab spring identify "Syrian revolution". In order to achieve the objective of the study, a questionnaire was designed as the main tool for collecting data. It includes (42) items divided into four variables (credibility, professional, quality and contributions). The sample comprises of 300 individuals’ that are selected randomly from all the media elites who work in Jordan. After the distribution of the questionnaire and data collection, the SPSS software was used to answer the study questions through the use of descriptive analysis. The study found that the degree of acceptance of the media elite to the work of citizen journalism ranked first compared to other sources of news, the role provided by the citizen journalist did not rise to the level of the other media, the respondents' estimates of the ability of the "citizen journalism" to fill the vacuum resulting from confusion and official misrepresentation through their technological tools such as the telephone came out clearly against this idea, as there is a significant weakness in the ability of the journalist to apply the standards used in the real media. In light of the results, the study recommends that the findings of the present study show that most of the news and information provided by citizen journalist not credible and not professional.